2018
DOI: 10.1039/c8cp03481h
|View full text |Cite
|
Sign up to set email alerts
|

A quantum-mechanical investigation of oxygen vacancies and copper doping in the orthorhombic CaSnO3perovskite

Abstract: In this study we explore the implications of oxygen vacancy formation and of copper doping in the orthorhombic CaSnO3 perovskite, by means of density functional theory, focusing on energetic and electronic properties. In particular, the electronic charge distribution is analyzed by Mulliken, Hirshfeld-I, Bader and Wannier approaches. Calculations are performed at the PBE and the PBE0 level (for doping with Cu, only PBE0), with both spin-restricted and spin-unrestricted formulations; unrestricted calculations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 98 publications
0
6
0
2
Order By: Relevance
“…Because of the charge-transfer nature of the emitting state that is strongly related to the CB bottom of the host, a temperature dependence linked to the band gap behavior is expected. Density functional theory calculations of the density of states (DOS) of CaSnO 3 and CaTiO 3 have demonstrated that the bottom of the CB is mainly formed by the 6s, 6p-Sn orbitals and the 3d-Ti orbitals, respectively. In this context, the temperature dependence of the band gap is usually characterized by a red shift by increasing the temperature, and a consequent red shift is expected for the MMCT emission band, raising the temperature.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Because of the charge-transfer nature of the emitting state that is strongly related to the CB bottom of the host, a temperature dependence linked to the band gap behavior is expected. Density functional theory calculations of the density of states (DOS) of CaSnO 3 and CaTiO 3 have demonstrated that the bottom of the CB is mainly formed by the 6s, 6p-Sn orbitals and the 3d-Ti orbitals, respectively. In this context, the temperature dependence of the band gap is usually characterized by a red shift by increasing the temperature, and a consequent red shift is expected for the MMCT emission band, raising the temperature.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Nevertheless, the B3LYP functional was also used to perform the simulations for the sake of comparison with the WC1LYP, because it is one of the most used functional to study crystalline materials. 50 Although the results have been somewhat favorable, they can still be improved. The preliminary structural and electronic results of both paths are described below.…”
Section: Choice Of Functional Basis Set and Strategies Of Calculationsmentioning
confidence: 99%
“…Perovskites are considered one of the most investigated materials for a variety of applications owing to their unique electronic, optical, magnetic, catalytic, and ferroelectric properties. ,, Among perovskites, CaSnO 3 (CSO), a high band gap semiconductor with a band gap of ∼4.7 eV is considered a highly diverse oxide owing to its unique structure, properties, and multifunctional applications. These included optoelectronics, catalysis, sensors, photodetectors, phosphors, lithium-ion batteries, and so forth. , Defects such as antisites, Schottky, oxygen vacancies (OVs), and so forth are abundantly present in CSO and are reported to have significant influence on its optical, catalytic, magnetic, and electrical properties. These defects can also lead to interesting photoluminescence properties in CSO as well, which is an extremely important area of research in these days for designing dopant- and lattice strain-free phosphors . Each defect has a specific role and can be engineered to achieve specific applications.…”
Section: Introductionmentioning
confidence: 99%